Morphology and phase composition of the molybdenum and iron oxides films on a substrate from anodic aluminum oxide - S. V. Dzenisiuk; A. M. Kudanovich; E. E. Kolesnik (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The study results of the surface morphology of molybdenum thin films phase composition and iron oxides formed on substrates from anodic alumina are presented. The formation of MoO3 polycrystalline film with orthorhombic crystal lattice and a grain size of 100 to 500 nm was carried out by thermal oxidation of the metal film in the temperature range 400-450 °C. The oxidation of iron films at temperatures of 550 to 750 °C formed the polycrystalline films of phase α-Fe2O3 (hematite) with a rhombohedral crystal lattice.